A Systems Thinking Approach to Managing Sustainment Phase Redesign Planning. Issue 1 (2nd January 2018) - Classi, Cal C.; Nowicki, David R.; Mansouri, Mo; Sauser, Brian J.; Randall, Wesley S.
Abstract: This study applies a systems thinking approach to sustainment-phase redesign planning for large-scale, complex, sustainment-dominated systems (SDSs) found in the airline, aerospace and defense, healthcare, and utilities industries. Maintaining the SDS's effectiveness throughout its long life presents a significant engineering and business challenge. This research contributes to the literature by developing an academically rigorous redesign-planning framework (RPF) through the lens of management and systems theories and the use of the grounded theory, research methodology. With the RPF, engineering managers can now simultaneously consider key issues, improvement opportunities, and risks of SDSs to develop and execute strategic, sustainment redesign plans that improve SDS performance at a lower lifecycle cost.